TRANSPARANSI DAN AKUNTABILITAS DALAM PENYALURAN BANTUAN SOSIAL (Studi di Desa Kurup Kecamatan Lubuk Batang Kabupaten Ogan Komering Ulu) - shindi asti ode; Aprilia Lestari; Eva Susanti (JURNAL DINAMIKA, 2026)
The distribution of social assistance is an important government program to improve public welfare and therefore must be implemented based on the principles of transparency and accountability. However, several problems remain in Kurup Village, Lubuk Batang District, Ogan Komering Ulu Regency, including uneven dissemination of information, limited public understanding of beneficiary selection procedures, and the need to improve the accuracy of beneficiary data. This study aimed to analyze the implementation of transparency and accountability in the distribution of social assistance in Kurup Village. The research was conducted in 2026 using a descriptive qualitative approach. Data were collected through observation, interviews, and documentation, and analyzed using data reduction, data display, and conclusion drawing. The findings indicate that transparency has been implemented through public information dissemination, village meetings, and publication of beneficiary lists, while accountability has been demonstrated through compliance with procedures, preparation of accountability reports, and documentation of distribution activities. Nevertheless, improvements are still needed in information dissemination, beneficiary data updating, and community participation. The study concludes that the implementation of transparency and accountability in the distribution of social assistance has been fairly effective but not yet optimal. Therefore, the village government is recommended to enhance information openness, regularly verify beneficiary data, and optimize communication media to ensure more accurate and accountable social assistance distribution.